2013
DOI: 10.1080/15389588.2013.813628
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Immediate Roadside Prohibitions for Drinking Drivers in British Columbia: Findings from Roadside Surveys

Abstract: The IRP program combined immediate short-term roadside suspensions with vehicle impoundment and monetary penalties to enhance the swiftness, certainty, and perceived severity of sanctions for drinking and driving. The introduction of these measures was associated with a substantial reduction in the prevalence of driving with a BAC over 50 mg/dL and driving with a BAC over 80 mg/dL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Drivers on the roads with BACs > .08 decreased by 59% while drivers with BACs > .05 decreased by 44% after the IRP law was in effect (Beirness and Beasley 2014). Another study of the IRP law in British Columbia showed significant average declines of alcohol-related crashes associated with the adoption of the law: 40.4% in fatal crashes, 23.4% in injury crashes, and 19.5% in property damage crashes.…”
Section: Three Priority Strategiesmentioning
confidence: 99%
“…Drivers on the roads with BACs > .08 decreased by 59% while drivers with BACs > .05 decreased by 44% after the IRP law was in effect (Beirness and Beasley 2014). Another study of the IRP law in British Columbia showed significant average declines of alcohol-related crashes associated with the adoption of the law: 40.4% in fatal crashes, 23.4% in injury crashes, and 19.5% in property damage crashes.…”
Section: Three Priority Strategiesmentioning
confidence: 99%
“…A 2012 roadside survey found that 82.5% of BC drivers were aware of the new legislation and 89.6% agreed that the new laws would make roads safer (Beirness and Beasley, 2014). Another 2012 survey found that public perception of police commitment to traffic enforcement had increased (Public Attitude Survey, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…2 After alcohol, cannabis is the most common substance implicated in impaired driving in Canada 3 ; data from the National Cannabis Survey (administered after cannabis became legal) indicated 14.7% of respondents had driven within 2 hours of consuming cannabis. 4 Before the legalization of cannabis, cocaine was the second most commonly detected unregulated substance after cannabis, 5 and 27.2% of fatally injured drivers had positive test results for central nervous system stimulants such as cocaine and methamphetamine. 2 While opioids are a less prevalent contributing substance to impaired driving, 3.1% of drivers surveyed in Ontario between 2011 and 2016 reported having driven under the influence of prescription opioids.…”
Section: Introductionmentioning
confidence: 99%